Celebrating the Megascale Proceedings of the Extraction and Processing Division Symposium on Pyrometallurgy in Honor of David G.C. Robertson - Mackey, Phillip; Grimsey, Eric.; Jones, Rodney; Brooks, Geoffrey; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
The volume contains more than 70 papers covering the important topics and issues in metallurgy today including papers as follows: keynote papers covering a tribute to David Robertson, workforce skills needed in the profession going forward, copper smelting, ladle metallurgy, process metallurgy and resource efficiency, new flash iron making technology, ferro-alloy electric furnace smelting and on the role of bubbles in metallurgical processing operations. Topics covered in detail in this volume include ferro-alloys, non-ferrous metallurgy, iron and steel, modeling, education, and fundamentals.
Keywords: Metals; Materials; Materials -- Analysis; Metals and Alloys; Materials Engineering; Characterization and Analytical Technique